A Computational Study of an Implicit Local Discontinuous Galerkin Method for Time-Fractional Diffusion Equations - Leilei Wei; Xindong Zhang (Abstract and Applied Analysis)
We propose, analyze, and test a fully discrete local discontinuous Galerkin (LDG) finite element method for a time-fractional diffusion equation. The proposed method is based on a finite difference scheme in time and local discontinuous Galerkin methods in space. By choosing the numerical fluxes carefully, we prove that our scheme is unconditionally stable and convergent. Finally, numerical examples are performed to illustrate the effectiveness and the accuracy of the method.